Modulation of the high-order chromatin structure by Polycomb complexes - Guo, Yiran; Wang, Gang Greg (Frontiers in Cell and Developmental Biology, 2022)
The multi-subunit Polycomb Repressive Complex 1 (PRC1) and Polycomb Repressive Complex 2 (PRC2) act, either independently or synergistically, to maintain and enforce a repressive state of the target chromatin, thereby regulating the processes of cell lineage specification and organismal development. In recent years, deep sequencing-based and imaging-based technologies, especially those tailored for mapping three-dimensional (3D) chromatin organization and structure, have allowed a better understanding of the PRC complex-mediated long-range chromatin contacts and DNA looping. In this review, we review current advances as for how Polycomb complexes function to modulate and help define the high-order chromatin structure and topologies, highlighting the multi-faceted roles of Polycomb proteins in gene and genome regulation.